PENGARUH KUALITAS LAYANAN AKADEMIK DAN KINERJA GURU TERHADAP KEPUASAN ORANG TUA MURID DI SEKOLAH - Tri Yuliarto (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
This study aims to examine the effect of academic service quality and teacher performanceon parents' satisfaction at Pembangunan Jaya Elementary School. The method used in this study is touse multiple linear regression with a qualitative. The results of this study indicate that the F count of165,637 with a significance value of 0.000 <α0.05 which means that H0 is rejected and H1 isaccepted. So this shows that there is a joint effect between all the independent variables on parents'satisfaction. If seen from the results of the T test, the academic service quality variable has acoefficient (β) of 0,864 with a sig value of 0,000. Significant value is smaller than α = 0.05 or 0,000<0.05 then the coefficient value (β) is positive, the teacher performance variable has a coefficient (β)of 0,873 with a sig value of 0.000. Significant value is smaller than α = 0.05 or 0.000 <0.05 then thecoefficient value (β) is positive. Calculation of the coefficient of determination obtained 79,3% andthe remaining 20,3% is influenced by other factors not included. Thus there is a positive influencebetween the quality of academic services and teacher performance on parent satisfaction inPembangunan Jaya Elementary School. The quality of academic services and teacher performancecontribute to generating good parent satisfaction in Pembangunan Jaya Elementary School.